LINGUISTIC SKETCHES (ON SOME PARTICULARITIES OF RUSSIAN SPOKEN LANGUAGE) - Bogdanova-Beglaryan, N.V. (Perm Federal Research Centre Journal, 2014)
The article considers some particularities of modern Russian oral communication: reduced forms of words like “ schas ” (now), “ tischa ” (thousand), etc.; verbal pause substitutes - hesitations like well…, sort of…, you know…, etc. which are inevitable in oral communication that is generated in the conditions of time insufficiency and which have different additional functions such as discursive, searching, rhythm-building, etc. The paper also deals with some lexical-semantic innovations known to all language users but traditionally considered below the norm and subject to elimination from the speech of a well-educated person. According to the author’s opinion, these linguistic phenomena should not be judged or denied; rather they should be recorded and analyzed since they illustrate the current language evolution we might be witnessing.